Influence of Menarche on Body Weight. A Systematic Review and Meta-Analysis. - Chiasson, Martine (Université d'Ottawa / University of Ottawa, 2014)
It has been shown that post-menarcheal girls are more likely to have increased their body weight and body mass index (BMI) than pre-menarcheal girls of the same age. In addition to the metabolic changes which occur during this interval, behavioural risk factors synergize to promote weight gain, putting adolescents at a much higher risk for excess weight gain and its associated health complications. Moreover, obesity during adolescence increase the risk of becoming an obese adult. A systematic review of English and French articles using MEDLINE, EMBASE, Cochrane, and CINAHL was conducted. Studies underwent a three level screening assessment by two independent assessors. Only studies with post-menarcheal weight change information were selected for data extraction and quality assessment, which was conducted by two independent reviewers. A meta-analysis was conducted for weight change and included 389 girls. Five studies discussed the effects of menarche on body weight change. Pooled results for three studies indicated a 10.39 kg increase from pre to post-menarche (95% CI, 9.16-11.62). The other two studies showed significant increases in body fat mass (p<0.05) and higher skinfolds measurements for post-menarcheal girls compared to pre-menarcheal girls. It is important to further explore the bio-psychosocial and environmental factors influencing the weight, especially the total fat mass and body fat distributions in young adolescent girls during the menarche transition in order to develop and evaluate preventive intervention strategies to prevent adolescent and adult obesity.
Keywords: Menarche; Weight gain; Adipose tissue; Obesity; Body fat distribution